The Command of Jilbāb in the Quran: Between Symbols of Piety and the Issue of Women's Exclusivity in Public Spaces - Najib, Muhammad Ainun; Hakim, Muhammad Naufal; Riyadi, Abdul Kadir; Wafiudin, M. Afif (Universitas Islam Negeri Raden Mas Said Surakarta, 2024)
This research is motivated by the fact that several cases have been found where veiled women experience marginalization both in society due to their style of veiling (niqab) and in the workplace. This is certainly contrary to the intent of the Qur'anic verse prescribing veiling, which is meant to protect women. Therefore, this study aims to re-examine the Qur'anic verses that discuss jilbāb by considering the inclusive space for women in the public sphere. This research uses a phenomenological approach, intertextual method, and Margot Badran's Islamic feminism theory. This study finds that the interpretation of the jilbāb verse shows a trend that the essence of the jilbāb is to protect the dignity and honor of women, with various interpretations of its form. Some interpret jilbāb as a cloth covering the head of a woman, while others see it as modest clothing. Initially, the protection prescribed by the jilbāb was understood internally as a command to cover the 'awrah. However, as cases of marginalization against veiled women have emerged, the jilbāb can now be understood not only as protection through covering the 'awrah but also as protection of women's rights legally and socially. Therefore, this study does not justify the marginalization of veiled women for any reason.